2020
DOI: 10.1194/jlr.ra119000594
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of 596 lipid species and genetic correlation with cardiovascular traits in the Busselton Family Heart Study

Abstract: CVD is the leading cause of death worldwide, and genetic investigations into the human lipidome may provide insight into CVD risk. The aim of this study was to estimate the heritability of circulating lipid species and their genetic correlation with CVD traits. Targeted lipidomic profiling was performed on 4,492 participants from the Busselton Family Heart Study to quantify the major fatty acids of 596 lipid species from 33 classes. We estimated narrow-sense heritabilities of lipid species/classes and their ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…Despite the expected influence of dietary intake on the circulatory lipids, contribution of genetic factors in endogenous regulation of lipid metabolism is well recognized. Studies using pedigree information and genetic data have shown that 10−60% of the variation in plasma levels of circulatory lipid species is contributed by the genetic factors, with considerable variation across lipid categories [ 12 , 75 77 ]. For example, in general, sphingolipids have higher heritability than glycerophospholipids, with ceramides having highest estimated SNP-based heritability (35–40%) and phosphatidylinositols with the least heritability (11–31%) [ 12 ].…”
Section: Genetic Regulation Of Lipidomementioning
confidence: 99%
“…Despite the expected influence of dietary intake on the circulatory lipids, contribution of genetic factors in endogenous regulation of lipid metabolism is well recognized. Studies using pedigree information and genetic data have shown that 10−60% of the variation in plasma levels of circulatory lipid species is contributed by the genetic factors, with considerable variation across lipid categories [ 12 , 75 77 ]. For example, in general, sphingolipids have higher heritability than glycerophospholipids, with ceramides having highest estimated SNP-based heritability (35–40%) and phosphatidylinositols with the least heritability (11–31%) [ 12 ].…”
Section: Genetic Regulation Of Lipidomementioning
confidence: 99%
“…Narrow-sense heritability for CERs in previous studies has been estimated at between 9 and 51% ( 18 , 19 ). Here, we have assessed a more extensive array of species to show that further CER[NS] and CER[NDS] are significantly heritable.…”
Section: Discussionmentioning
confidence: 93%
“…CER[N(16)S(18)]) have been suggested as novel biomarkers of cardiovascular death ( 16 ), type-2 diabetes and insulin resistance ( 17 ). The contribution of genetic factors to plasma variation in some CER species has been investigated ( 5 , 6 , 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the serum of patients with a clinical diagnosis of HF with preserved ejection fraction (HFpEF), the most common form of HF and also strongly associated with diabetes, in The Alberta Heart Failure Etiology and Analysis Research Team (HEART) project showed reduced SM compared to non-HF controls ( 136 ). These sphingolipids seemed to have no relationship to conventional risk factors such as diastolic blood pressure, systolic blood pressure, BMI and waist-hip ratio, suggesting they may be used as more specific markers to identify high-risk patients especially likely to have CVD ( 137 140 ).…”
Section: Sphingolipids As Emerging Biomarkers In Assessing Cardiovascmentioning
confidence: 99%